Does the visibility of a congenital anomaly affect maternal–infant attachment levels?. Issue 4 (4th October 2016) - Boztepe, Handan; Ay, Ayşe; Kerimoğlu Yıldız, Gizem; Çınar, Sevil
Abstract: Purpose: To determine whether congenital anomaly visibility affects maternal–infant attachment levels. Design and Methods: The study population consisted of mothers who had infants with cleft lip/palate or congenital heart anomalies who were receiving treatment in a university hospital. The data were collected using the Structured Questionnaire Form and the Maternal Attachment Inventory. Results: Statistically significant differences in maternal–infant attachment levels were observed between infants with cleft lips/palates and healthy infants and between infants with congenital heart anomalies and healthy infants. Practice implications: It is important to apply appropriate nursing interventions for these mothers during the postpartum period.